TEKNIK PEER-CORRECTION TERHADAP KEMAMPUAN MENULIS PUISI SISWA KELAS VIII SMP SWASTA JAMBI MEDAN - Weandy Nabilla NR (Jurnal Bastra (Bahasa dan Sastra), 2025)
Poetry is a type of literary work. One of the writing skills that students must master is presenting ideas, feelings, and opinions in the form of poetry text, written or orally, paying attention to the building blocks of poetry. Several studies show that the ability to write poetry is relatively low. One solution that can be done is to apply a learning technique that can improve students' poetry writing abilities. One of them is the peer-correction technique. This research aims to determine the ability of class VIII students at Jambi Medan Private Middle School before and after using the peer-correction technique, to assess the effect of peer-correction on their ability to write poetry. The method used is a quasi-experiment (Quasi Experiment). This research uses normality tests, homogeneity tests, and hypothesis tests. The research results show that students' ability to write poetry texts after applying the peer-correction technique is included in the perfect category, the application of the Peer-Correction learning technique has a positive effect on increasing the ability to write poetry texts. As previously stated, the average score for the ability to write poetry texts before using the Peer-Correction model (pre-test) is in the poor category, namely 58.50, while the average score for the ability to write poetry texts after using the Peer-Correction technique (post-test) classified in the good category, namely 79.33. It can be concluded that peer-correction learning techniques have a significant effect on the ability to write poetry texts.